Pengaruh Penggunaan Media Spotify Terhadap Keterampilan Menyimak Teks Bahasa Jerman Level A1.1 Mahasiswa Program Studi Pendidikan Bahasa Jerman Universitas Pattimura - Malawat, Nayla Naftali; Marantika, Juliaans E. R.; Akihary, Wilma (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
Listening skills are basic German language skills that are important. This study aims to describe whether there is an effect of using Spotify media on listening skills for German text at level A1.1. This study uses the Quasi Experimental research method, where researchers only use one group as the object of research by using Spotify as the media applied to the object of research, with the research design used is Pre-Test & Post-Test. The instrument used in this study is the German listening skills test (hören) Level A1.1 from Goethe (Pre-test and Post-test). The results showed that there was a significant increase in the average score of the test results before and after treatmen. t, where the pretest average for all respondents was 55.29 while the posttest average was 77,94. The results of further calculations showed that the calculated t value of 1,960 is greater than the t table value of 1.746, thus the null hypothesis is rejected. This means that there is an effect of using Spotify media on listening skills for German text at level A1.1. in improving listening skills for German text at level A1.1 for students of the Pattimura University German Language Education Study Program. This indicates that the use of Spotify as a digital media can function well in language learning, both receptive and also productive.